2009
DOI: 10.1111/j.1365-3059.2008.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of QoI resistance in Botrytis cinerea and identification of two types of mitochondrial cytochrome b gene

Abstract: Botrytis cinerea field isolates collected in Japan were screened for resistance to Qo inhibitor fungicides (QoIs). Of the 198 isolates screened, six grew well on a medium containing azoxystrobin, a QoI, when salicylhydroxamic acid, an alternative oxidase inhibitor, was present. The resistance mutation in the cytochrome b gene ( cytb ) was characterized. All QoI-resistant isolates had the same mutation (GGT to GCT) in cytb that led to the substitution of glycine by alanine at position 143 of cytochrome b , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
89
1
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 27 publications
10
89
1
8
Order By: Relevance
“…However, other mutations conferring lower levels of resistance may be selected in these fungi, such as F129L in P. teres (30). These findings may account for the presence of the G143A substitution only in strains lacking the intron in Botrytis group II in our sample and in Californian and Chinese isolates (40) and in Japanese strains isolated from various host plants for which no fitness cost associated with strobilurin resistance could be found (7). In our population data set, G143A was not found in any of the 27 group I strains.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, other mutations conferring lower levels of resistance may be selected in these fungi, such as F129L in P. teres (30). These findings may account for the presence of the G143A substitution only in strains lacking the intron in Botrytis group II in our sample and in Californian and Chinese isolates (40) and in Japanese strains isolated from various host plants for which no fitness cost associated with strobilurin resistance could be found (7). In our population data set, G143A was not found in any of the 27 group I strains.…”
Section: Discussionmentioning
confidence: 76%
“…Some shifts in susceptibility to multisite fungicides and fluazinam have also been recorded in ornamental plants and vegetables (44). Moreover, field strains of B. cinerea resistant to inhibitors of mitochondrial complexes II and/or III have recently been detected (7,38,40,54,65). Finally, strains displaying MDR have been isolated from French and German vineyards (42,44).…”
mentioning
confidence: 99%
“…Botrytis cinerea is particularly interesting, since the same species presents two types of cytochrome b gene; some field isolates contain intron bi2, while others do not. The mutation G143A has been reported only in the latter populations (1,17). These observations suggested that the presence or absence of intron bi2 might affect the occurrence of the G143A mutation.…”
mentioning
confidence: 98%
“…The case of Botrytis cinerea is different; two types of CYTB gene were found in Japanese populations of the grey mould pathogen, one with three introns and the other with an additional intron (Bcbi-143/144 intron) inserted between the 143rd and 144th codons. All QoI-resistant isolates showed the G143A mutation whereas the isolates possessing the Bcbi-143/144 intron were QoI-sensitive (Banno et al, 2009). The possession of such an intron may guarantee a low risk of QoI resistance but it might not always be fixed in pathogen populations.…”
Section: Unknown Mechanismsmentioning
confidence: 99%